Design for how people think using brain science to build better products - Whalen, John (O'Reilly Media, 2019)
User experience doesn't happen on a screen; it happens in the mind, and the experience is multidimensional and multisensory. This practical book will help you uncover critical insights about how your customers think so you can create products or services with an exceptional experience. Corporate leaders, marketers, product owners, and designers will learn how cognitive processes from different brain regions form what we perceive as a singular experience. Author John Whalen shows you how anyone on your team can conduct "contextual interviews" to unlock insights. You'll then learn how to apply that knowledge to design brilliant experiences for your customers